ANALISIS VARIABEL INTERNAL DAN EKSTERNAL DALAMPENGELOLAAN ZAKAT PADA BAZNAS KABUPATEN/KOTA DI SUMATERA BARAT - Fahlefi, Rizal (State Institute for Islamic Studies Batusangkar, 2017)
The purpose of this study is to determine the strengths, weaknesses, opportunities, and obstacles BAZNAS district / city in West Sumatra in the management of zakat. The research design used is descriptive qualitative. Sources of research data consisted of district / municipality BAZNAS administrators, provincial BAZNAS administrators, local government authorities, and related documents. Data were collected through interview and documentation techniques. The data obtained were analyzed using SWOT analysis. The results show that the strength of BAZNAS districts in West Sumatera is the commitment of management, management autonomy, UPZ formation, continuous socialization, volunteer zakat, zakat fund transparency and program innovation. The weakness of the BAZNAS is insufficient SDM, double positions, lack of muzaki and mustahik databases, the role of UPZ is not optimal yet, the collection is still focused on Zakah on the profession of civil servants, the distribution of consumptive zakat is still dominant, and infrastructure facilities are inadequate. BAZNAS's opportunities are regional regulation, enormous zakat potential, cooperation with religious organizations, public trust, increased civil servant salary / allowances and rapidly growing information technology. The obstacles faced by BAZNAS are the area of work of BAZNAS is very broad, operational budget is minimal, rejection from some scholars and community leaders, direct distribution of zakat, and involvement of others in socialization is still lacking.